2012
DOI: 10.1021/jf304006y
|View full text |Cite
|
Sign up to set email alerts
|

Silver Ions Release from Antibacterial Chitosan Films Containing in Situ Generated Silver Nanoparticles

Abstract: This study aims to develop antimicrobial films consisting of chitosan and silver nanoparticles that are homogeneously distributed throughout the polymer matrix. Nanoparticles were generated in situ during the neutralization of the chitosan acetate film with sodium hydroxide. The temperature of neutralization and the concentration of silver in the film were crucial determinants of the shape and size of the nanoparticles. Neutralized films exhibited antimicrobial activity against Escherichia coli and Staphylo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 23 publications
(44 reference statements)
1
45
0
1
Order By: Relevance
“…Nanosilver may: 1) bind to cell membrane, membrane proteins, and DNA bases, leading to the disruption of normal function (blue dotted line); 2) release silver ions, affecting membrane, DNA, and proteins (red dotted line); 3) generate reactive oxidative species (ROS), which may also affect DNA, cell membrane, and membrane proteins (black dotted line). [26,60] [56,57] Silver ions can bind to thiol groups (ASH) of the protein forming stable ASAg bonds, which can alter the 3D structure of proteins and block active binding sites.…”
Section: Role Of Silver Ionsmentioning
confidence: 99%
“…Nanosilver may: 1) bind to cell membrane, membrane proteins, and DNA bases, leading to the disruption of normal function (blue dotted line); 2) release silver ions, affecting membrane, DNA, and proteins (red dotted line); 3) generate reactive oxidative species (ROS), which may also affect DNA, cell membrane, and membrane proteins (black dotted line). [26,60] [56,57] Silver ions can bind to thiol groups (ASH) of the protein forming stable ASAg bonds, which can alter the 3D structure of proteins and block active binding sites.…”
Section: Role Of Silver Ionsmentioning
confidence: 99%
“…These bacteria have the ability to survive and proliferate on common surfaces for up to nine weeks, and can be easily spread through direct contact. [7][8][9] While this approach can be effective, some limitations include the release of toxic species into the environment, and the gradual exhaustion of the biocide, resulting in inactivity as well as subinhibitory concentrations of biocide near the surface and in the environment that will facilitate the development of bacterial resistance. Coatings for medical devices such catheters and implants also have great potential to reduce the bacterial infections that result from these objects.…”
mentioning
confidence: 99%
“…[59][60][61] A number of literatures have reported that silver nanoparticles incorporated with chitosan-based matrix present a broad spectrum of antimicrobial activity to inhibit both Gram-positive and Gram-negative bacteria including multidrug-resistant pathogens such as P. aeruginosa, ampicillin-resistant E. coli, erythromycin-resistant Streptococcus pyogenes, methicillinresistant S. aureus (MRSA) and vancomycin-resistant S. aureus (VRSA). [62][63][64][65][66][67][68][69] However, the application of silver nanocomposite and chitosan as antifungal effect in Cm and Ac is rare. This study shows a selective inhibition by chitosan and silver nanoparticles-chitosan composite, suggesting that the cellular wall composition or modification of Cm and Ac is distinct.…”
mentioning
confidence: 99%